"HASH"ing out pancreatitis: the new increasingly common culprit. Issue 4 (4th July 2019) - Chandy, Joel; Hassan, Ammar; Sciarra, Michael
ABSTRACT: Acute pancreatitis is a serious, potentially life threatning inflammatory disorder of the pancreas usually caused by alcohol use or gallstones. Other causes include certain drugs (such as antibiotics, antihypertensive medications, and immunosuppressants) and extremley high triglyceride levels.Cannabis use has been identified as an uncommon cause of acute pancreatitis. However, due to its rarity in the general population, it has been low on practitioners' differential diagnosis. As a result, the incidence is likely underrepresented as these patients' recurrent episodes of pancreatitis are likely labeled as idiopathic when in fact they are not. This case report highlights the importance of keeping a wide differential when considering possible causes of pancreatitis.